2016
DOI: 10.1177/0891988716666379
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cognitive Impairment in Fragile X-Associated Tremor/Ataxia Syndrome

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset neurodegenerative disease with motor, psychiatric, and cognitive manifestations that occurs in carriers of the fragile X mental retardation 1 (FMR1) gene premutations. This was a retrospective chart review of 196 individuals (127 men, 69 women) with FXTAS. Forty-six (23%) participants were cognitively impaired, of whom 19 (10%) had dementia. Risk factors for dementia were examined (CGG repeat size; alcohol, benzodiazepine, and opioid use; diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
0
14
0
1
Order By: Relevance
“…CGG repeat length had previously been associated with FXTAS clinical features, such as the age of onset of tremor and executive dysfunction (Cornish et al, 2011 ). The repeat size is also considered a risk factor for developing FXTAS dementia (Seritan et al, 2016 ). Others reported a correlation between age and CGG repeat length, as they found that male carriers with over 100 CGG repeats are more susceptible to the effects of aging on measures of executive function (Cornish et al, 2011 ).…”
Section: Clinical Manifestations Of Poi In General and Ovarian Dysfunmentioning
confidence: 99%
“…CGG repeat length had previously been associated with FXTAS clinical features, such as the age of onset of tremor and executive dysfunction (Cornish et al, 2011 ). The repeat size is also considered a risk factor for developing FXTAS dementia (Seritan et al, 2016 ). Others reported a correlation between age and CGG repeat length, as they found that male carriers with over 100 CGG repeats are more susceptible to the effects of aging on measures of executive function (Cornish et al, 2011 ).…”
Section: Clinical Manifestations Of Poi In General and Ovarian Dysfunmentioning
confidence: 99%
“…Clinical presentation, age of onset, and severity of FXTAS are heterogeneous. A larger CGG repeat size in PM carriers predicts earlier age of onset and perhaps earlier death [ 40 , 41 , 65 ]. Symptoms in females are milder since they have two X chromosomes [ 39 , 66 ].…”
Section: Clinical Presentation Of Fxtasmentioning
confidence: 99%
“…Behavioral self-regulation, verbal fluency, working memory, remote recall, declarative verbal learning memory, visuospatial function, temporal sequencing, information processing speed, and general intelligence, specifically nonverbal intellectual quotient, are often found to be impaired in individuals with FXTAS [ 88 , 89 , 90 ]. The impairment is correlated with CGG repeat number [ 65 , 88 , 89 ] and it worsens over time. Milder cognitive impairment can sometimes affect non-FXTAS carriers who are also aging [ 90 ].…”
Section: Clinical Presentation Of Fxtasmentioning
confidence: 99%
“…Neuropathic signs were tested using the Total Neuropathy score modified to exclude nerve conduction velocity testing [9]. FXTAS stage was noted at baseline [10].…”
Section: Clinical and Laboratory Evaluationsmentioning
confidence: 99%